Low-grade adenosquamous carcinoma of the breast - Gloria Zhang; Nancy Fong (Elsevier, 2021)
Abstracte: Low-grade adenosquamous carcinoma is categorized as a rare variant of metaplastic carcinoma of the breast. It has some distinct, although not specific, histological features and immunophenotype. It shares characteristics with both benign and malignant breast lesions and often poses diagnostic challenges. Different from most triple-negative breast carcinomas, low-grade adenosquamous carcinoma has a relatively indolent clinical behavior. It is important to recognize this lesion for appropriate management. Due to its rarity, many aspects of this lesion remain unclear. Further studies are necessary for a more accurate diagnosis and better management.